Evaluation of Ki‐67 and Bcl‐2 antigen expression in breast carcinomas of women treated with raloxifene - Lopes‐Costa, P. V. (Cell Prolif, 2010)
Objectives:  To evaluate the effect of raloxifene on Ki‐67 and Bcl‐2 antigen expression in operable, stage II, oestrogen‐receptor‐positive invasive ductal breast carcinomas. Materials and methods:  Twenty post‐menopausal women who had taken 60 mg of raloxifene daily for 28 days prior to definitive surgery were enrolled in the investigation. Two tumour samples were obtained by incisional biopsy during the study, one at the time of confirmation of diagnosis of invasive ductal carcinoma and evaluation of oestrogen receptor status, and the other 29 days later, at the time of definitive surgery. Immunohistochemistry was performed on tumour samples, prior to and after raloxifene treatment, to evaluate Ki‐67 and Bcl‐2 expression. Friedman and McNemar tests were used for statistical analysis of the data, significance being established at 5%. Results:  Mean percentage of Ki‐67‐stained nuclei was 24.86 ± 2.95 prior to raloxifene treatment and 13.33 ± 1.52 after treatment (P < 0.001). Prior to raloxifene treatment, only 9/20 cases (45%) were classified as Bcl‐2‐positive, whereas after treatment, 17/20 (85%) were classified as Bcl‐2‐positive (P < 0.013). Conclusions:  Raloxifene treatment significantly reduced Ki‐67 antigen expression and increased Bcl‐2 expression in breast carcinomas of post‐menopausal women.